Hole and electron transport materials: A review on recent progress in organic charge transport materials for efficient, stable, and scalable perovskite solar cells - B. Gopal Krishna; Dhriti Sundar Ghosh; Sanjay Tiwari (Chemistry of Inorganic Materials, 2023)
Charge transporting materials are essential for fabricating stable and efficient perovskite solar cells. The high-temperature processing, surface defects, and low mobility are common issues in inorganic charge transport materials which can hinder the fabrication of low-cost, efficient, and stable perovskite solar cells. Dopants increase the processing cost of the hole transport materials. Surface defects are observed in the high-temperature processed inorganic electron transport materials. There is a need to develop organic compounds for charge transportation in perovskite solar cells. Herein, the advancements in the organic materials for charge transport in the perovskite solar cells are reviewed. The low-cost processing, better solubility, efficient charge mobility, tunable molecular orbitals, and better stability of organic compounds are some properties for their utilization as charge transport materials in perovskite solar cells. Organic small molecules, polymers, and phthalocyanine compounds can be utilized as dopant-free hole transport materials. Fullerene and non-fullerene derivatives like C60, C70, azaacenes, indacenodithiophene, polymers, and rylene diimides are promising electron transport materials. The functionality, engineering, charge transport properties, and device characteristics of different organic materials are discussed. The review will offer a forecast for improving device stability and efficiency in terms of architecture, engineering, and materials to realize the commercialization of perovskite solar cells soon.